Exosome-loading miR-205: a two-pronged approach to ocular neovascularization therapy - Hui-ying Zhang; Qiu-yang Zhang; Qing Liu; Si-guo Feng; Yan Ma; Feng-sheng Wang; Yue Zhu; Jin Yao; Biao Yan (Journal of Nanobiotechnology)
Abstract Pathological neovascularization is a hallmark of many vision-threatening diseases. However, some patients exhibit poor responses to current anti-VEGF therapies due to resistance and limited efficacy. Recent studies have highlighted the roles of noncoding RNAs in various biological processes, paving the way for RNA-based therapeutics. In this study, we report a marked down-regulation of miR-205 under pathological conditions. miR-205 potently inhibits endothelial cell functions critical for pathological neovascularization, including proliferation, migration, and tube formation. Furthermore, miR-205 strengthens the endothelial barrier, thereby reducing vascular leakage. In mouse models of retinal and choroidal neovascularization, miR-205 administration effectively suppresses abnormal blood vessel formation and leakage. Mechanistically, miR-205 directly targets VEGFA and ANGPT2, which are key drivers of pathological neovascularization. To improve delivery, we successfully loaded miR-205 into exosomes derived from mesenchymal stem cells. This innovative approach avoids cytotoxicity while preserving therapeutic efficacy in both cellular and animal models. Collectively, our findings highlight miR-205 as a promising therapeutic for ocular neovascularization, with exosome delivery offering a novel and efficient strategy for treating vision-threatening vascular diseases. Graphical Abstract